2021
DOI: 10.1002/acp.3852
|View full text |Cite
|
Sign up to set email alerts
|

The effect of source credibility on bullshit receptivity

Abstract: Summary Pseudo‐profound bullshit pertains to grammatically and syntactically correct but meaningless sentences, that, due to syntactical correctness appear as made to communicate something and research shows that people deem them profound. However, the effect of differing source credibility on bullshit profoundness evaluations has, to our knowledge, not yet been tested. We presented participants with pseudo‐profound bullshit alone and with authors of different credibility. In order to partly replicate and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
(72 reference statements)
3
15
1
Order By: Relevance
“…We also found no significant effect of source, which was surprising given that past studies have found that pseudo-profound bullshit is rated as more profound when attributed to credible or expert sources than when no source is given (Gligori c & Vilotijevi c, 2020; Hoogeveen et al, 2022;Ili c & Damnjanovi c, 2021). However, much of the bullshit that people are exposed to is encountered online (Simpson, 2019) and the way that we presented our stimuli is noticeably dissimilar to the visual formats more common to the ways in which misinformation is often presented online, particularly on social media (e.g., memes, fake news headlines, social media comments, etc.).…”
Section: Resultscontrasting
confidence: 60%
See 3 more Smart Citations
“…We also found no significant effect of source, which was surprising given that past studies have found that pseudo-profound bullshit is rated as more profound when attributed to credible or expert sources than when no source is given (Gligori c & Vilotijevi c, 2020; Hoogeveen et al, 2022;Ili c & Damnjanovi c, 2021). However, much of the bullshit that people are exposed to is encountered online (Simpson, 2019) and the way that we presented our stimuli is noticeably dissimilar to the visual formats more common to the ways in which misinformation is often presented online, particularly on social media (e.g., memes, fake news headlines, social media comments, etc.).…”
Section: Resultscontrasting
confidence: 60%
“…Hoogeveen et al (2022) found a significant effect of source for pseudo‐profound bullshit statements when presented in a visual format more similar to online memes that people often encounter while on social media. Likewise, Ilić and Damnjanović (2021) presented bullshit statements in a similar way to how inspirational quotes are often shared online, with detailed references (randomly assigned to each statement) which included an author name followed by a year, a location where the statement was purportedly made, and a source (e.g., book, interview, or letter) for each statement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rachev and colleagues (2022) examine whether the risky-choice and attribute framing effect, describing variation in preference under different presentations of the same problem (Tversky & Kahneman, 1981), occurs and shows similar relations to the willingness and ability to think in line with rational norms across two samples. The willingness and ability to think in line with rational norms were represented by two constructs; namely, actively open-minded thinking (Haran et al, 2013) and bullshit receptivity (e.g., Ilić & Damnjanović, 2021). The authors found that the susceptibility to framing was associated with these two constructs in both samples, with a stronger negative relation of susceptibility to framing with actively open-minded thinking in Bulgaria than in North America.…”
Section: How the Present Papers Contribute To Open Science And Shed L...mentioning
confidence: 99%